2021
DOI: 10.3390/min11080860
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Occurrence of Rare Earth Elements in Mining Waste and Mine Water: A Review

Abstract: Μining waste, processing by-products and mine water discharges pose a serious threat to the environment as in many cases they contain high concentrations of toxic substances. However, they may also be valuable resources. The main target of the current review is the comparative study of the occurrence of rare earth elements (REE) in mining waste and mine water discharges produced from the exploitation of coal, bauxite, phosphate rock and other ore deposits. Coal combustion ashes, bauxite residue and phosphogyps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…Even though the REE recovery from SM generated positive impacts in several categories, high freshwater eutrophication-resulting from the release of phosphate to the water-and ionizing radiation potentials could be encountered during the processing. In order to minimize these negative impacts, the reuse of other SM including fly ash, coal ash, and bauxite (red mud) could be considered, as they were demonstrated to be promising materials for REE extraction [66].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the REE recovery from SM generated positive impacts in several categories, high freshwater eutrophication-resulting from the release of phosphate to the water-and ionizing radiation potentials could be encountered during the processing. In order to minimize these negative impacts, the reuse of other SM including fly ash, coal ash, and bauxite (red mud) could be considered, as they were demonstrated to be promising materials for REE extraction [66].…”
Section: Discussionmentioning
confidence: 99%
“…Since REE are present in low concentrations in mining wastewaters and acid mine drainage, adsorbents such as cellulosic materials and ion exchange materials could be more useful as part of extraction/preconcentration and/or purification processes. Pyrgaki et al [136] in a recent review described mining waste and mine water as promising sources of REE if their extraction is coupled with the simultaneous removal of toxic pollutants. These authors reported very high concentrations of ∑REE+Y of 77 to 1957.7 µg/g in coal combustion ashes, bauxite residue and phosphogypsum, and 1.6 to 24.8 µg/ml in mine discharges from different coal and ore mining areas around the globe As the primary and secondary REE ores are getting depleted, alternative sources such as the recycling of e-waste for a substantial recovery of REE gained prominence in recent times [140].…”
Section: Acid Mine Drainagementioning
confidence: 99%
“…For underground coal slurry, the physical properties change significantly from one mine site to another [22]. It is essential to understand the coal slurry's chemical compositions for the chosen of flocculent.…”
Section: Composition Analysis and Slurry Viscosity Testmentioning
confidence: 99%
“…The major positive ions (Ca 2+ , Na + , Mg 2+ , K + ) and the major negative ions (F − , Cl − , NO 3 − , HCO 3 − , SO 4 2− ) are detected in the coal mine water [20,21]. Water hardness is an index to evaluate the alkaline elements in the water solutions [13,19,22]. In order to avoid any water pollution, essential methods should be adopted to remove these ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation